Detection of carbapenemase-producing Klebsiella pneumoniae in a hospital in northern Peru - Díaz-Sipión, Roberto (2020)
Objetive. Communicate the first report of Klebsiella pneumoniae producing carbapenemases. The study: Microbiological diagnosis using phenotypic methods: double disc synergy, modified Hodge test, immunochromatography and carbapenemic inactivation. Findings: Four isolates (urine 3 and blood 1) of carbapenemase-producing K. pneumoniae were confirmed, which also presented a MIC of 4 and> = 8 for ertapenem and> = 16 µg / mL at imipenem and meropenem. Conclusion: Standardized phenotypic methods are useful in the confirmation of carbapenemases and with it an alternative for the best taking of therapeutic options and epidemiological surveillance.